Are official forecasts of output growth in the EU still biased? - David Cronin; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2020)
A reason for revising the EU fiscal rules in the early 2010s was to improve member states' forecasts against a background of documented biases in official projections. Using data from Stability and Convergence Programmes and the European Commission's Spring Forecasts, evidence is presented which indicates deficiencies in official forecasting in the EU arising under the new enhanced EU fiscal framework, with forecasts being irrational and a pessimistic bias. Recently highlighted obstacles to the way in which independent fiscal institutions operate in member states and the EU fiscal rules' emphasis on ex-ante fiscal plans may contribute to such forecasting performance.
Keywords: C23; E37; E62; 330; Official forecasts; forecasting bias; EU fiscal rules